Analisis Kinerja Jaringan Jalan Di Kawasan Pelabuhan Pulau Baai Kota Bengkulu Untuk Rencana Jalur Mitigasi Bencana Tsunami - Maha Deta Winusi; Hardiansyah; Lindung Zalbuin Mase; Rena Misliniyati; Fepy Supriani (Fakultas Teknik Universitas Pasir Pengaraian, 2025)
Pulau Baai Port in Bengkulu City is a densely active area with a high risk of being affected by a tsunami disaster. This study aims to model the road network and analyze its performance during evacuation using the Four Step Model method. Surveys were conducted to assess existing conditions, build evacuation movement scenarios, and model the effect of road capacity improvements. The results show an RÂ² value of 0.8502, indicating that the modeling is valid compared to real field conditions. The evacuation modeling produced the highest degree of saturation on several road segments, reaching 0.91, 0.75, and 0.70, indicating a high risk of congestion during evacuation. Increasing road capacity proved effective in reducing traffic density, lowering the degree of saturation to 0.78, 0.69, and 0.54. Therefore, road widening can serve as an effective solution for planning better evacuation routes.